Fathers’ parenting in women’s workforce family - Fadillah, Galih Fajar; Hidayati, Anni Nurul; Nafi, Ahmad (Pusat Studi Gender dan Anak, 2023)
The parenting style a father provides differs from the parenting pattern a mother provides. Children whom their fathers raise tend to develop creative abilities to justify their behavior. In the Polan area, Polanharjo District, children whose fathers educate them while their mothers work as migrant workers have the freedom to organize study activities, worship, eat, and even rest. Most importantly, the child carries out all the daily routines, even though they do not match the expectations. This study aims to find out how the parenting style of a father whose wife is female workforce provides attention and fulfills their child's rights. The subjects were three fathers who educated their children from 12 to 18 years old. Interviews, documentation, and observation are applied as data collection techniques. This study showed that fathers also play a significant role in shaping children's character. Modify the father's role not only as the backbone of the family but also as a discussion partner regarding career planning and crucial decision-making. The father's parenting style does not entirely ignore the child's feelings and desires; instead, it encourages the child to reconsider the effects of their decisions and attitudes. This study showed that the three subjects tended to use democratic parenting styles.